2011
DOI: 10.1111/j.1369-7625.2011.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Close to the bench as well as at the bedside: involving service users in all phases of translational research

Abstract: Aim The paper aims to develop a model of translational research in which service user and other stakeholder involvement are central to each phase.Background ÔTranslationalÕ is the current medical buzzword: translational research has been termed Ôbench to bedsideÕ research and promises to fast-track biomedical advances in the service of patient benefit. Models usually conceive of translational research as a ÔpipelineÕ that is divided into phases: the early phase is characterized as the province of basic scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
100
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 48 publications
0
100
0
4
Order By: Relevance
“…39 Callard et al 172 argue that failing to have PPI in the early stages of translational research may result in failing to capitalise on the potential contributions lay representatives could make, including ensuring that the end product of bench research must be appropriately designed for the end-user, and that ethical issues arising between any DOI: 10.3310/hsdr03380 HEALTH SERVICES AND DELIVERY RESEARCH 2015 VOL. 3 NO.…”
Section: Patient and Public Involvement: Is It Always Needed?mentioning
confidence: 99%
See 1 more Smart Citation
“…39 Callard et al 172 argue that failing to have PPI in the early stages of translational research may result in failing to capitalise on the potential contributions lay representatives could make, including ensuring that the end product of bench research must be appropriately designed for the end-user, and that ethical issues arising between any DOI: 10.3310/hsdr03380 HEALTH SERVICES AND DELIVERY RESEARCH 2015 VOL. 3 NO.…”
Section: Patient and Public Involvement: Is It Always Needed?mentioning
confidence: 99%
“…Not everyone believed that PPI was essential to each stage of a study or was persuaded that benefits far outweighed potential risks, particularly for studies nearer the laboratory end of the 'bench to bedside continuum'. 172 Arguments for seeing PPI as less essential or more risky included there being a lack of evidence of PPI effectiveness in this type of research. However, our analysis suggested that underpinning this assertion were several researcher beliefs, including that lay representatives would not be comfortable with the more basic science and that they lack the knowledge to understand it.…”
Section: Patient and Public Involvement: Is It Always Needed?mentioning
confidence: 99%
“…Longerterm outcomes typically have complex causes that are difficult to trace back to one research study, let alone the engagement of patients or other stakeholders in the research enterprise [27]. Beyond clarifying the goals for Research quality and research process [28,43,44] Improved quality and validity from engaging patients [45] Enhanced credibility and improved the research [46] 85% of patients and researchers (n = 59) agreed that the quality of research improved [41] New funding and funding opportunities [41,47] Patients' contributions on research proposal, lay language summary and encouragement for reapplying [48] None reportedResearch topic, priorities and/or resource allocation become more appropriate/relevant to patients [38,[49][50][51][52] Patients suggested research ideas and provided feedback on usefulness of research to the benefit of the research process [48] Improved relevance of research ideas and topics [45] Identification of study topics by patients was an impetus for research [53] None reportedResearch questions, hypotheses, interventions and medical technologies become more relevant/usable for patients [1,54,55] Patients' experiential knowledge helped shape research question [23] None reportedResearch design, methods and study procedures become more appropriate, sensitive and ethically acceptable [9,17,21,34,38,41,51,[55][56][57] Patient research partners provided insight/access into social networks, patient organizations and the healthcare field [23] Patients helped translate scientific jargon into plain language materials [23] Patients provided feedback on intervention design and data collection instrument [48] None reported Recruitment, accrual rates and retention improves [9,…”
mentioning
confidence: 99%
“…As advisors, they provide enhanced understanding of barriers and facilitators of participation and the environmental and social contexts in which the research will take place. Their knowledge favorably influences the agenda, setting, validity, and feasibility of the research design from the informed consent process to data collection and outcome measures (26). From a pragmatic perspective, participatory research is essential.…”
Section: Stakeholder Engagementmentioning
confidence: 99%